PENGARUH LAMA PENAMBAHAN BAWANG PUTIH (ALLIUM SATIVUM LINN.) DALAM MINYAK GORENG BEKAS PAKAI TERHADAP PENURUNAN BILANGAN PEROKSIDA - Dian Wuri Astuti; Muji Rahayu; Temu Safitri Sari (Universitas Muhammadiyah Semarang, 2014)
Cooking oil belongs to a staple food which is frequently needed and used by society. To use itrepeatedly at high temperatures, accompanied by contact with air and water in the fryingprocess will result in damage to it by peroxide of formation. The amount of peroxide is the mostsignificant one to determine the degree of damage to it. The content of peroxide in it that hasbeen used repeatedly, can be reduced by adding antioxidants. Garlic is one of the plants thatcontain allicin and alliin which are antioxidants. This study aims to determine the influencefrom the longing of the addition of garlic toward used cooking oil to decrease the amount ofperoxide. This research is true experiment and the amount of peroxide determined by iodometrictitration. The independent variable is the longing of the addition of garlic and the dependentvariable is the amount of peroxide with Pre and Post Test with Control Group design. The dataobtained are analyzed by using Anova One Way for statistical test with the significance level of5%. The decreases of the amount of peroxide in used cooking oil after long treatments whichare the addition of garlic for 1 hour, 2 hours, 3 hours, and 4 hours, respectively are 11.18%,55.27%, 55.36%, and 100%. From the analysis of the data, it is obtained that the effect of garlicon the reduction of the amount of peroxide is 78.4%.